2022
DOI: 10.1111/1750-3841.16376
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites and chemometric study of Perilla (Perilla frutescens) from different varieties and geographical origins

Abstract: Perilla (Perilla frutescens, PF) is an annual labiaceae herb that can be used as vegetable, seasoner, and herb, which mainly includes red PF (P. frutescens var. crispa) and green PF (P. frutescens var. frutescens). Red and green Perilla is mainly used for medicine and food, respectively. In order to explore the differences between these two Perilla cultivars and the effects of origin on them, we studied the components of 130 Perilla samples from different origins by ultra‐high performance liquid chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Kaempferol and ferulic acid were abundant in the E3 extract. Other studies have confirmed the presence of these compounds in different varieties of Perilla frutescens [29][30][31].…”
Section: Discussionmentioning
confidence: 61%
“…Kaempferol and ferulic acid were abundant in the E3 extract. Other studies have confirmed the presence of these compounds in different varieties of Perilla frutescens [29][30][31].…”
Section: Discussionmentioning
confidence: 61%
“…P. frutescens leaves have multiple uses as medicinal materials, vegetables, and spices. They are known to contain a diverse range of chemical components, including flavonoids and polysaccharides ( Fiedor and Burda, 2014 ; Holt et al, 2005 ; Li et al., 2022 ). The flavonoid compounds in plants have distinct functions in response to specific developmental stages or abiotic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, P. frutescens leaves come in various colors such as green and purple. The purple leaves are rich in anthocyanin content and are used as a food pigment ( Yoshida et al., 1990 ; Fujiwara et al., 2018 ; Li et al, 2022 ). On the other hand, the green leaves of P. frutescens contain a high content of bioactive compounds and are often utilized in various applications such as food, skin creams, and medications for atopic dermatitis ( Komatsu et al., 2016 ; Edge et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…After consuming Perilla frutescens extracts, polyphenols may be taken into the circulation and integrated into LDL, according to in vitro studies [ 75 , 76 ]. In addition, it must be considered that Perilla frutescens contains a variety of antioxidants, including polyphenols, vitamin E, and carotenoids [ 77 , 78 , 79 ]. Certain hydrophilic antioxidants link to phospholipids or proteins on the LDL periphery, while hydrophobic antioxidants attach nearer to the LDL nucleus, according to previous research [ 80 , 81 ].…”
Section: Antioxidant and Hypolipemiant Effectsmentioning
confidence: 99%